CAR T-Cell Therapy Is Effective but Not Long-Lasting in B-Cell Lymphoma of the Brain - Li, Tongjuan; Zhao, Lei; Zhang, Yuanyuan; Xiao, Yi; Wang, Di; Huang, Liang; Ma, Liya; Chen, Liting; Liu, Songya; Long, Xiaolu; Meng, Fankai; Zhu, Xiaojian; et al. (Frontiers in Oncology, 2020)
Advanced central nervous system (CNS) lymphoma is an exclusion criterion for most chimeric antigen receptor (CAR) T-cell studies due to the associated levels of neurotoxicity. In this study, we described five patients with chemorefractory B-cell CNS lymphoma who received CAR19 and CAR22 T-cell “Cocktail” therapy and follow-up for 6 to 16 months. All patients experienced cytokine release syndrome (CRS). Two patients experienced CAR T-cell-related encephalopathy syndrome (CRES), which was controllable. The best response was observed in 2 patients, who successfully achieved complete remissions (CR), and the other 3 patients achieved partial remissions (PR). Four patients had progressive disease (PD) after remission. In addition, one CR patient and one PD patient accepted CAR T-cell infusion following hematopoietic stem cell transplantation therapy in the third month and were in ongoing remission for 14 and 6 months of follow-up, respectively. The targeted antigens in 2 patients were still positive, and CAR T-cells were reboosted in the cerebrospinal fluid (CSF) after PD, but a small number of CD3-positive T-cells were observed to infiltrate into the tumor. Our study indicates the efficacy of CAR T-cell therapy for CNS lymphoma with an acceptable safety profile; however, the remission did not last long, perhaps due to the tumor immunosuppressive microenvironment (TME) of the CNS. CAR T-cell therapy should be combined with other treatments to help improve the TME of cerebral lymphoma.